The relationship between law-related education diversion and juvenile offenders’ social- and self-perceptions - Fox, James W. (American journal of criminal justice, 1994)
A main purpose of Law-Related Education (LRE) programming in juvenile justice is to teach attitudes and perceptions that are inconsistent with delinquent behavior. This study examines the perceptions of juvenile offenders who participated in Kentucky’s LRE diversion program. Using a semantic differential instrument and a quasi-experimental design, pretest and posttest data were obtained on juveniles’ perceptions of themselves, their parents, their neighbors, their best friends, judges, teachers, and the police. Analyses of pre to post change and comparisons of the perceptions displayed by divertees with those displayed by a comparable group of high school students revealed some favorable outcomes associated with LRE participation. The recidivism of divertees over a one year follow-up period was also low. The limitations and implications of the study are discussed. The study concludes that LRE may be a viable diversionary option in juvenile justice.